3D printing and epoxy-infusion treatment of curved continuous carbon fibre reinforced dual-polymer composites. (1st April 2022) - Zhang, Haoqi; Wu, Jiang; Robert, Colin; Ó Brádaigh, Conchúr M.; Yang, Dongmin
Abstract: A manufacturing technique was developed to fabricate curved continuous carbon fibre reinforced composites based on 3D printing and epoxy-infusion treatment. Composite preforms were first manufactured by material-extrusion based 3D printing of continuous carbon fibre reinforced thermoplastic polyamide-6 (PA-6) filaments. Powder thermoset epoxy was added to the preforms to fill up the gaps, remove air voids and enhance the interfacial bonding through a traditional vacuum bagging and oven curing process. Uniaxial tensile tests showed that the stiffness and strength of the printed composites were increased by 29.3% and 22.1%, respectively, compared to the thermoplastic-only composite specimens. The epoxy-infusion treatment technique was also adopted to manufacture composites with curved fibre alignment and investigate the performance of 3D printed notched specimens under uniaxial tension. It was shown that the placement of continuous carbon fibres along the principal stress trajectories increased the failure strength and the fracture toughness of the composites by 81% and 157% respectively, compared to the unidirectional and concentric placement methods.